2000
DOI: 10.1053/jlts.2000.6356
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hemodynamics and Perioperative Cardiopulmonary-Related Mortality in Patients With Portopulmonary Hypertension Undergoing Liver Transplantation

Abstract: In the setting of moderate to severe pulmonary artery hypertension, orthotopic liver transplantation (OLT) may be complicated by pulmonary hemodynamic instability and cardiopulmonary mortality. We retrospectively studied the relationship between cardiopulmonary-related mortality and initial (untreated) pre-OLT pulmonary hemodynamics in 43 patients with portopulmonary hypertension who underwent attempted OLT. Thirty-six patients were reported in 18 peer-reviewed studies, and 7 patients underwent OLT at our inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
405
0
27

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 536 publications
(445 citation statements)
references
References 34 publications
13
405
0
27
Order By: Relevance
“…Elevated MPAP has been the most important parameter in discussing the multicenter diagnostic implications of POPH. 5,8 However, various reasons for elevated MPAP exist in the setting of liver disease (hyperdynamic circulatory state, increased central volume). Our data clearly demonstrate that elevated MPAP alone is not specific for the diagnosis of POPH, supporting the current diagnostic criteria that must include PVR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated MPAP has been the most important parameter in discussing the multicenter diagnostic implications of POPH. 5,8 However, various reasons for elevated MPAP exist in the setting of liver disease (hyperdynamic circulatory state, increased central volume). Our data clearly demonstrate that elevated MPAP alone is not specific for the diagnosis of POPH, supporting the current diagnostic criteria that must include PVR.…”
Section: Discussionmentioning
confidence: 99%
“…CTP class A (score 5-6) is less severe than CTP class C (score 10-15). 5 The MELD score is quantitative, being derived from a formula with the variables serum total bilirubin, international normalized ratio, and serum creatinine. 17 The CTP classification and MELD score determinations were obtained based on data available at the time of the right heart catheterization in a retrospective manner.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAH can substantially increase the risk associated with liver transplantation and usually PAH is a contraindication if P pa is .35 mmHg and/or PVR is o250 dynes.s.cm -5 [206,212]. It has been suggested that PAH-specific drug therapy should be used to improve haemodynamics prior to liver transplantation, but the effects on the outcome of liver transplantation have not been evaluated sufficiently.…”
Section: Therapymentioning
confidence: 99%
“…The primary focus of therapy is on control of pulmonary pressures with vasodilator therapy and improved right ventricle (RV) function, with consideration of LT if MPAP of 35 mm Hg or lower can be maintained. 5,[11][12][13][14][15] Thus, HPS and POPH have divergent clinicopathologic features and management.…”
mentioning
confidence: 99%